Board of directors remuneration and corporate performance - Bortoli, Cassiana; Dombroski, Jéssica de Fátima; Soares , Rodrigo Oliveira (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Background: The board of directors is considered one of the main corporate governance mechanisms of companies, that is, it represents the interests of shareholders to directors, especially regarding corporate performance. It is known that an important mechanism for aligning interests is remuneration. Purpose: Thus, the study analyzed the effect of board of directors' remuneration on the financial performance of Brazilian companies listed on B3. Method: The sample included 121 non-financial companies from 2010 to 2019. The proxies for financial performance used were ROA and ROE, and the variable of interest consisted of the average total remuneration of the board of directors. Panel data regressions by fixed effects were estimated, and for robustness, the models were also estimated by the Generalized Method of Moments (GMM System). Results: The results indicated that board of directors' remuneration has no effect on the financial performance of companies. Conclusions: The findings contribute to the literature and stakeholders by demonstrating that the predominant agency problems in national companies are in line with the argument that in emerging economies the need to minimize conflicts between agent and principal is small due to the shareholder concentration that tends to greater monitoring of hired managers.